Greek Thrace Xoraxane Romane. (25th July 2014) - Adamou, Evangelia; Arvaniti, Amalia
Abstract : Romani is an Indo-Aryan language spoken in several European countries as well as in the Americas, Asia and Australia, showing substantial dialectal variation. This illustration deals with Xoraxane Romane (Turkish Romani) spoken in Greek Thrace. Xoraxane Romane, which belongs to the Vlax branch of Romani, has been heavily influenced by contact with Turkish and also shows influences from Greek. As a result, Xoraxane Romane exhibits a mixed system that includes phonemes borrowed from both Turkish and Greek but without exhibiting complex phonological phenomena such as Turkish vowel harmony.